2020
DOI: 10.1177/0022034520968750
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenesis of Male Oral Submucous Fibrosis Alters Salivary Microbiomes

Abstract: Most oral squamous cell carcinoma (OSCC) tumors arise from oral premalignant lesions. Oral submucous fibrosis (OSF), usually occurring in male chewers of betel quid, is a premalignant stromal disease characterized by a high malignant transformation rate and high prevalence. Although a relationship between the inhabited microbiome and carcinogenesis has been proposed, no detailed information regarding the oral microbiome of patients with OSF exists; the changes of the salivary microbiome during cancer formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Although the within-group diversity was not significantly different among cohorts, a decreased trend of core microbiome from healthy or OVH to OSCC was observed when the total diversity of each cohort (gamma diversity) was considered. Consistent with the previous studies that the richness of core species among healthy individuals was 9.6-13.1% ( Takeshita et al., 2016 ; Willis et al., 2018 ) and it decreased to 5.96% in the OSCC patients with oral submucous fibrosis ( Chen et al., 2020 ), our study also showed the decrease of richness from 12.53% in the normal cohort to 6.34% in the OSCC cohort. Together, the gamma diversity as an indication reflecting dysbiosis of the core salivary microbiome is effectually linked to the progression of oral cancer.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Although the within-group diversity was not significantly different among cohorts, a decreased trend of core microbiome from healthy or OVH to OSCC was observed when the total diversity of each cohort (gamma diversity) was considered. Consistent with the previous studies that the richness of core species among healthy individuals was 9.6-13.1% ( Takeshita et al., 2016 ; Willis et al., 2018 ) and it decreased to 5.96% in the OSCC patients with oral submucous fibrosis ( Chen et al., 2020 ), our study also showed the decrease of richness from 12.53% in the normal cohort to 6.34% in the OSCC cohort. Together, the gamma diversity as an indication reflecting dysbiosis of the core salivary microbiome is effectually linked to the progression of oral cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Several amino acid biosynthesis pathways (isoleucine, tryptophan, arginine, ornithine, valine, and methionine) were enriched in the normal group, particularly in Zhao’s and our datasets ( Figure S5 ), suggesting potential up-regulation of those amino acids in the healthy cohort (and correspondingly down-regulation in the OSCC cohort), which is consistent with previous studies ( Yang et al., 2018 ). Several previous studies also suggested the dysregulation of ornithine, arginine, and polyamine synthesis in the salivary microbiome during oral carcinogenesis from the healthy or precancerous stage ( Chen et al., 2020 ; Sharma et al., 2020 ). In addition, Zhao’s and our study showed that the biosynthesis of lipids and fatty acids, especially cis-vaccenate and gondoate are enriched in the OSCC cohort ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…A recently published paper by Chen et al (2021) provided new insights into salivary microbiome and microbial metabolite alterations during the malignant transformation of oral submucous fibrosis (OSF). These findings gave new direction to the understanding of carcinogenesis mechanism of oral squamous cell carcinoma in the background of OSF (OSCC-OSF).…”
mentioning
confidence: 99%